A vespa de Humaitá: a propaganda de guerra no periódico Cabichuí - Sergio Willian de Castro Oliveira Filho (Navigator)
The studies associated to the Humaitá Fortress are of fundamental importance for the understanding of the conflict denominated War of the Triple Alliance against the government of Paraguay. However, the historiographical operation regarding the bastion of Humaitá can go beyond its walls, geography, cannons and soldiers. On that place, on May 13, 1867, one of the main organs of the Paraguayan trench press emerged: the Cabichuí. The aim of this article is to analyze the main characteristics of this newspaper and how the propaganda of war, present in its pages, was constituted as important element wrapped in the history of the fortification of Humaitá.